2015
DOI: 10.1002/ese3.56
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted transesterification of refined and crude palm oils using heterogeneous palm oil mill fly ash supported calcium oxide catalyst

Abstract: Ultrasound-assisted transesterification of refined palm oil (RPO) and crude palm oil (CPO) to produce biodiesel using a palm oil mill fly ash supported calcium oxide (CaO) catalyst is studied in this work. The reaction time is significantly reduced from a maximum of 360 min under conventional mixing to just 30 min with the use of ultrasound. Under ultrasonic cavitation, the required catalyst loading and methanol to oil molar ratio to produce comparable yields and fatty acid methyl esters (FAME) conversions as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Short production cycle, low production costs, the esterification rate and low environmental pollution; industrial difficulty. [22,39,66,67] Ultrasound-assisted production of biodiesel Z. Zhao et al free enzymatic transesterification of Macauba (Acrocomia aculeata) coconut oil by using a commercial immobilized lipase (Novozym 435).…”
Section: Direct Mixing Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Short production cycle, low production costs, the esterification rate and low environmental pollution; industrial difficulty. [22,39,66,67] Ultrasound-assisted production of biodiesel Z. Zhao et al free enzymatic transesterification of Macauba (Acrocomia aculeata) coconut oil by using a commercial immobilized lipase (Novozym 435).…”
Section: Direct Mixing Methodsmentioning
confidence: 99%
“…Song produced biodiesel by using a two‐step enzymatic method of energy microalgae; the method yielded 80.1% biodiesel from microalgae oil by using methanol to oil molar ratio of 4:1, solution pH of 6, and speed of 180 rpm at 35 °C for 10 h. Ultrasound is an auxiliary tool introduced in chemical reactions and synthesis methods to promote the synthesis of biodiesel . Ho et al studied ultrasound‐assisted transesterification of refined palm oil (RPO) and crude palm oil (CPO) to produce biodiesel by using palm oil mill fly ash‐supported calcium oxide as catalyst. For RPO, the maximum biodiesel yield and fatty acid methyl ester (FAME) conversion rates of 85.23% and 97.02% were obtained through ultrasound‐assisted transesterification with 60% ultrasonic amplitude, 30 min reaction time, 4 wt.% catalyst loading, and 9:1 methanol to oil molar ratio.…”
Section: Production Methods Of Biodieselmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the conversion diminished at 90 min (81 %). Ho et al [25] found that, after 40 min, the conversion decreased in the ultrasound-assisted transesterification of palm oil. This finding suggests that the ultrasound irradiation enhances the reaction rate compared with the conventional reaction.…”
Section: Influence Of the Reaction Timementioning
confidence: 99%